Lima: A Creole City, a Mestizo City - Ricardo Pinto-Bazurco Mendoza (Ибероамериканские тетради)
From a historical and cultural perspective, Lima, the capital of Peru, is a city of many contrasts whose past is inextricably intertwined with its present and future prosperity. Lima, like all Latin American cities, has a rich history that can be forgotten if its citizens fail to cherish it. Therefore, the literary works of different Peruvian authors and especially those of Raúl Porras Barrenechea are especially relevant: they are full of nostalgia, yet at the same time take a critical approach to the city’s history, which helps us contemplate Lima’s place in the world and the best course for its future development as the city is constantly transforming. Lima, a city of creole and mestizo origins, is a space that invites us to reflect on how it seeks to live up to its traditions and cultural legacy. From a contemporary city dweller’s point of view, citizens and authorities should work together to achieve greater prosperity and improve the quality of life, which is important for the future of not only Lima, but also Peru and Latin America.